Tingkat Pengembangan Dan Daya Terima Cupcake Dari Beberapa Varietas Tepung Jagung Terfermentasi - Sukeksi, Yoshima Intan, Pramudya Kurnia, STP, M.Agr, Rusdin Rauf, S.TP., M.P (2015)
Background: The food made from wheat flour led to the economy and nutrition problem. Efforts to anticipate the use of wheat flour is to produce flour based food local, for example modified corn flour with the fermentation. The fermented corn flour as the ingredient of cupcake can compose the development and different acceptabillity with wheat flour. Objective: This research has the purpose to know the level of development and acceptibility on makes cupcake from some variety of flour corn fermentation. Research Method: This research using of the complete random planning with 4 methods. Each method was done three times, that is cupcake of flour corn fermented variety of pop, cupcake of flour corn fermented variety of sweetcorn, cupcake of flour corn fermented variety of hybrid and cupcake of wheat flour as control. Result: The result of this research indicates that the best level of development of the cupcake from sweet corn, that is 84,43% and the acceptibility by corn cupcake show color and scent of the most popular is the varieties of pop. Taste and texture of the cupcake the most popular is the varieties of hybrid, while on occupancy toward all of them the most popular is the varieties of pop. Conclusion: The level development on cupcake show the difference of statistic test, on occupancy of statistic has the differance in color, texture and acceptibility.